Technology literacy education based PHP2D local wisdom program in Cicadas village Indonesia - Maulinda, Tiara Nurul; Nugraha, Santi; Hadina, Nurasih; Megawati, Erna (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The activity called PHP2D Tali Rafika (Literacy Park Based on Local Wisdom) in Cicadas Village aims to provide education to residents about technological literacy that can be used to improve the welfare of residents. This activity was motivated by the condition of the partner villagers who had not been able to take full advantage of technology. The method used in this activity is in training, which contains the theory and practice of utilizing social media such as YouTube, Instagram, and Facebook as media for marketing citizen products. The tools used in this training include portable computers, wifi, devices, and slides. The program could increase citizens' technological literacy skills, which is indicated by the ability of citizens to use social media to improve their welfare.